Efeitos ecológicos das estradas na conservação de espécies na America Latina: estado do conhecimento, desafios e oportunidades - Pinto, Fernando Antônio Silva (2019)
Roads can cause adverse ecological effects for many animal species worldwide, mainly due to habitat fragmentation and mortality from collision with vehicles. Much of the knowledge about such effects come from temperate regions in countries of the northern hemisphere, with different socioenvironmental realities. In this study, we analyzed the ecological effects of roads on vertebrate species in Latin America over different approaches. In the first article, I carried out a systematic literature review in order to assess the current state of knowledge about the ecological effects of roads on vertebrates in Latin America, to identify gaps of knowledge and, then to propose an agenda for future research. After reviewing nearly 200 articles, we identified a trend in the increase of publications in the last decade concentrated mainly in South America, with studies at the individual level (mortality), focused mainly on mammals. Few studies tried to understand the effects on the population level and gene level, neither evaluation of mitigation measures. We recommended a two-speed approach to research: a first, focused on quantifying how species (individuals) interact with roads as well as their implications at the population level, and a second that assess the vulnerability of the species to the roads at regional or national scales. In the second paper, I analyzed the effects of habitat fragmentation and road-kills over giant-anteater (Myrmecophaga tridactyla) populations in Brazil. We use a spatially-explicit population model that reaches outputs approximations on minimum patch size and maximum road density required for giant anteater populations viability. The results showed that minimum patch size estimations varying between 247 and 498 km² and the maximum road densities between 0.21 and 0.55 km/km². Furthermore, we showed that unsuitable areas for the species persistence ranged between 32 to 36% of their range in Brazil.